KESALAHAN BERBAHASA INDONESIA TULIS PADA MAHASISWA THAILAND (STUDI ATAS PEMBELAJAR BIPA DI PPB UIN SUNAN KALIJAGA) - Ening Herniti (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2017)
The Indonesian language mistake to write Thai speakers is a complicated issue for foreign speakers because they tend to discuss writing out spoken language. This language error will result in the failure of the message due to misinterpretation, not understanding what is being said, and redundancy of words or phrases. This study focuses more on writing errors because errors in writing languages are more easily detected. This is because writing languages require punctuation completeness, diction accuracy, and structural precision. This paper describes forms of Indonesian error in Thai linguists' written language. Data were obtained from the Thai learner's daily duty book. The data is then identified and classified based on the error. Data were analyzed qualitatively-prescriptive. That is, the data is analyzed by describing the forms of errors that are guided by the rules of using the correct written Indonesian language. The conclusion of this study shows that the errors of written language conducted Thai learner occurs at all levels of language, namely the level of phonology, morphology, syntax, semantics, and discourse. At the phonological level, language errors are found in pronunciation due to phoneme changes. At the morphological level, there are errors in the absence of affixes. At the syntactic level, errors are in placement conjunction errors, absence of prepositions, and improper structures. At the semantic level, the hyperbolic meaning and the error of diction. At the discourse level, there is a misplacement of place deixis. In addition, there are also errors in the application of the Indonesian Spelling (EBI) rule which includes errors in writing of absorbed words and misplacement of punctuation.